Injury, illness, and mental health problems during the 2023 FIFA Women`s world cup - Lu, D.; Clarsen, B.; Whalan, M.; Serner, A.; Duffield, R.; Fulcher, M.; Reid, D.; Toohey, L.; Veith, S.; Wilke, C.; Mosler, A. (Science and Medicine in Football, 2025)
Our study aimed to describe the patterns and characteristics of injuries and illnesses incurred during the FIFA Women`s World Cup 2023 (FWWC2023). Team medical personnel recorded all injuries, illnesses, and mental health problems requiring medical attention, plus match, and training exposure into a centralised FIFA database using recent consensus-based methodology. Of the 32 teams at FWWC2023, 26 teams participated in the study, including 536 of 742 players. A total of 161 medical-attention injuries (incidence rate (IR): 14.2 per 1000*h [95% CI: 12.1 to 16.6]) and 59 time-loss injuries (IR: 5.2 per 1000*h [CI: 4.0 to 6.7]) were reported. Time-loss match injury IR was 14.0 per 1000*h [CI: 8.9 to 21.1] and training IR 2.2 per 1000*h [CI: 1.3 to 3.3]. The knee and thigh were the most frequently injured locations, while the lower leg created the highest overall time-loss burden. Time-loss injuries were mostly reported from contact mechanisms (59%), particularly with an opponent. There were 41 medical-attention illnesses (IR: 4.2 per 1000 player-days [CI: 3 to 5.6]) and 8 time-loss illnesses (IR: 0.8 per 1000 player-days [CI: 0.3 to 1.6]) reported. Respiratory illnesses (16 medical-attention and 7 time-loss) were the most frequent, with a burden of 1.2*days lost per 1000 player days [CI: 0.4 to 2.2]. The IR of mental health problems was low (0.2 per 1000 player-days [CI: 0.02 to 0.7]). Compared to previous international tournaments of both sexes, injury incidence and burden at the FWWC2023 was low.